Analysis of mi guerrade España with a gender perspective: the relationships between women and men in militia during Spanish Civil War (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
In order to study the history of women “Self-writtings” are a very important source since they provide private information about their authors. Thanks to these sources/writings one can get closer to the experiences and reflections of their female writers. Besides, one can also study the tautness between the gender rules established in a specific historical moment and women’s initiatives regarding those rules. This article is aimed at contributing to the study of the Spanish civil war from a gender perspective, with the analysis of Mi Guerra de España, the memories of Mika Etchebéhère, an argentine militiawoman. This is a particular useful case that shows the reorganization of the relationships between genders during that historical period.
Keywords: momories; militiawoman; gender; Spanish civil war; feminism